2012
DOI: 10.1097/gme.0b013e3182325e4b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of red ginseng supplementation on menopausal symptoms and cardiovascular risk factors in postmenopausal women

Abstract: RG could be an attractive herbal dietary supplement for relieving menopausal symptoms and conferring favorable effects on markers of cardiovascular disease in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 31 publications
0
86
0
1
Order By: Relevance
“…MCF-7 cells, however, estrogenic activity of KRG was not manifested in vivo study such as female Sprague–Dawley rats [13]. In human (women), KRG showed improvements in the Kupperman index and in the menopause rating scale scores [14]. Taken together, we can suspect effects of KRG on female reproduction or gynecological complaints via phytoestrogenic structures or characteristics of triterpenoid saponins in KRG.…”
Section: Introductionmentioning
confidence: 99%
“…MCF-7 cells, however, estrogenic activity of KRG was not manifested in vivo study such as female Sprague–Dawley rats [13]. In human (women), KRG showed improvements in the Kupperman index and in the menopause rating scale scores [14]. Taken together, we can suspect effects of KRG on female reproduction or gynecological complaints via phytoestrogenic structures or characteristics of triterpenoid saponins in KRG.…”
Section: Introductionmentioning
confidence: 99%
“…Several evidence suggests that nutrition is very important for decreasing CVD risk factors in postmenopausal women, and phytochemical agents found in herbs and plants can be beneficial effect [20-22]. Garlic has been used to treat hypertension, coronary diseases, and CVD, in adult since ancient times [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…One systematic review suggested that the evidence on efficacy of ginseng for managing menopausal symptoms was limited [89]. Three randomized controlled trials (RCTs), which were included in the review, tested the efficacy of KRG compared with placebo, and their results showed superior effects of KRG on sexual arousal and global health [90], [91], [92]. Another trial reported favorable effects of ginseng supplements on well-being and depression as compared with placebo [93].…”
Section: Effects On Erα and Erβmentioning
confidence: 99%